2014
DOI: 10.1021/la404976k
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of C60 Fullerene Solubility in Aqueous Solution

Abstract: In this work, we report that the surface hydroxylation of C 60 molecules is the most likely mechanism for pristine C 60 fullerenes/C 60 fullerene aggregate stabilization in water, being independent of the method of C 60 fullerene aqueous solution preparation. ■ INTRODUCTIONNanocarbon materials are used in a wide variety of biomedical applications, including biosensorics, targeted drug delivery, chemotherapy, cellular imaging, and diagnostics. 1 For example, the pristine C 60 fullerenes as a unique class of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 30 publications
6
68
0
2
Order By: Relevance
“…The numerous and sometimes conflicting results of experimental 5,14,[16][17][18][19][20][21][22][23][24][25][43][44][45][46][47][48][49] and theoretical [73][74][75][76][77][78][79] investigations demand such a comparison. Indeed, the theoretical calculations often predict strong interaction between C 60 and water (as a recent example, the work by Choi et al 77 may be proposed), which may be considered as a type of expressed hydration, whereas the coagulation data indicate the hydrophobic nature of the fullerene hydrosols.…”
Section: Fullerene Organosols Vs Hydrosolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The numerous and sometimes conflicting results of experimental 5,14,[16][17][18][19][20][21][22][23][24][25][43][44][45][46][47][48][49] and theoretical [73][74][75][76][77][78][79] investigations demand such a comparison. Indeed, the theoretical calculations often predict strong interaction between C 60 and water (as a recent example, the work by Choi et al 77 may be proposed), which may be considered as a type of expressed hydration, whereas the coagulation data indicate the hydrophobic nature of the fullerene hydrosols.…”
Section: Fullerene Organosols Vs Hydrosolsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Therefore, it is important to better understand their behavior in a solution. One of the specific features of fullerenes is their ability to form aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Зразки (об'ємом 500 мкл) були за-литi у кварцевi кювети (Hellma Analytics) з товщи-ною 1 мм, якi знаходились при температурi 20 ∘ С. За фоновi зразки були використанi розчинники та їх сумiшi без фулерену, так званi, буфернi зразки. Для калiбрування iнтенсивностi розсiяння нейтро-нiв був використаний стандартний ванадiєвий зра-зок [30,31]. Обробка отриманих даних здiйснюва-лась програмою SAS у режимi згладжування [32].…”
Section: матерIали та методиunclassified
“…In contrast, much less work about the pollution control of PHF has been reported up to now. On the other hand, Prylutskyy et al (2014) indicated that the origin of fullerene solubility in water was probably based on the surface hydroxylation of fullerene molecules; therefore, nC 60 could be considered as fullerene aggregates with a certain amount of hydroxyls on the outer surfaces. Furthermore, when exposed to the environment, fullerenes and nC 60 could be transformed into PHF by many factors (e.g., long-term mixing, ultraviolet radiation, and interaction with microbes and oxidants) Qu et al, 2010;Chae et al, 2014).…”
Section: Introductionmentioning
confidence: 99%